Macrophage‐mediated psoriasis can be suppressed by regulatory T lymphocytes. Issue 3 (November 2016) - Leite Dantas, Rafael; Masemann, Dörthe; Schied, Tanja; Bergmeier, Vera; Vogl, Thomas; Loser, Karin; Brachvogel, Bent; Varga, Georg; Ludwig, Stephan; Wixler, Viktor
Abstract : Linked Commentary:Poschke et al. J Pathol 2016; DOI: 10.1002/path.4820 . Abstract: We recently described an inducible human TNF transgenic mouse line (ihTNFtg) that develops psoriasis‐like arthritis after doxycycline stimulation and analysed the pathogenesis of arthritis in detail. Here, we show that the skin phenotype of these mice is characterized by hyperproliferation and aberrant activation of keratinocytes, induction of pro‐inflammatory cytokines, and infiltration with Th1 and Treg lymphocytes, particularly with macrophage infiltration into lesional skin, thus pointing to a psoriasis‐like phenotype. To reveal the contribution of T cells and macrophages to the development of TNF‐mediated psoriasis, ihTNFtg mice were crossbred into RAG1 KO mice lacking mature T and B cells. Surprisingly, the psoriatic phenotype in the double mutants was not reduced; rather, it was enhanced. The skin showed significantly increased inflammation and in particular, increased infiltration by macrophages. Consequently, depletion of macrophages in RAG1 KO or wild‐type mice led to decreased disease severity. On the contrary, depletion of Treg cells in wild‐type mice increased both psoriasis and the number of infiltrating macrophages, while adoptive transfer of Foxp3‐positive cells into RAG1 KO or wild‐type mice decreased both the development of psoriasis and macrophage infiltration. Thus, we conclude that Treg lymphocytes inhibit the pro‐inflammatory activity of macrophages, which are the major immune effector cells in hTNF‐mediated psoriasis. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.